A review on highlights and feasibility studies on solar energy utilization in Malaysia - Abd Wahid, Siti Sufiah; Ramli, Mohd Sufian; Ahmad Noorden, Zulkarnain; Hassan, Khairul Kamarudin (Universiti Teknologi MARA, Johor, 2016)
Over the years, solar has been one of the main substitutes of electricity resources worldwide including Malaysia in effort to reduce the dependency on the conventional fossil fuel. In this paper, the status of solar energy in Malaysia Plans is investigated while the techniques used in various techno-economic and economic feasibility studies on the implementation of solar energy system are analyzed. The state of awareness and understanding on solar energy among Malaysians is also determined. It has been found that a mathematical formulation method as well as an iterative technique which both consider lots of uncertainties are capable in optimally designing a photovoltaic, PV system while minimizing the cost. Meanwhile, a financial model using probabilistic and sensitivity analysis is able to provide the potential investors with the profitability of a PV project. Finally, several surveys has proven that Malaysian people are lack of awareness, information thus interest on solar technology. Therefore, in evaluating the feasibilities of a PV system, it is suggested that considerations on all solar-related variables must be taken into account while at the same time the Government of Malaysia, GoM should play the main role by providing more aggressive programmes and schemes in order to educate and expose Malaysian citizens with knowledge and skills on solar energy.